Asymptotically free AdS3/CFT2 - Balthazar, Bruno; Giveon, Amit; Kutasov, David; Martinec, Emil J. (The journal of high energy physics, 2022)
A bstract We propose a new AdS 3 /CFT 2 duality, in which the bulk string theory has a target spacetime AdS 3 times a squashed three-sphere S ♭ 3 , and the dual CFT 2 is a symmetric product of sigma models on ℝ ϕ × S ♭ 3 , deformed by a ϕ -dependent ℤ 2 twist operator. The duality maps the asymptotic region of AdS 3 to the region ϕ → ∞ , where the twist interaction in the CFT 2 turns off. The AdS 3 backgrounds in question have R AdS < ℓ s , and so lie on the string side of the string/black hole correspondence transition. As a consequence, the high energy density of states consists of a string gas in AdS 3 rather than an ensemble of BTZ black holes. This property allows us to derive the dual CFT 2 by a systematic analysis of the worldsheet string theory on AdS 3 .